Improving the Management of Adult Patients with Acute Ankle Fractures in Malawi: An Examination of Providers' Knowledge and Treatment Strategies. Issue 4 (22nd October 2020) - Agarwal-Harding, Kiran J.; Kapadia, Ami; Banza, Leonard; Chawinga, Mabvuto; Mkandawire, Nyengo; Kwon, John Y.
Category: Trauma; Ankle; Other Introduction/Purpose: The burden of trauma is growing worldwide, especially in low-income countries. In Malawi, ankle fractures are common and may receive inadequate treatment due to limited surgical capacity and provider knowledge of evidence- based treatment guidelines. We sought to examine ankle fracture management in Malawi, identify providers' knowledge gaps, and address these knowledge gaps in ways that were relevant to the Malawian context. Methods: This study had three phases. First, we performed a baseline assessment of orthopaedic providers' knowledge of anatomy, injury identification, and ideal treatment methods. Second, we observed providers' treatment strategies while they cared for adult patients with ankle fractures over a five-week period at a large central hospital. We performed blinded, post-hoc reviews of patient x-rays and compared our treatment recommendations to the plans and rationales of Malawian providers. Third, we implemented an educational course addressing the knowledge gaps we identified, performed pre- and post-course knowledge assessments, and launched a standardized protocol for ankle fracture management in Malawi. Results: In our baseline assessment, we identified significant knowledge gaps in identification of common injuries on x-ray and ideal treatment practices. In our observations of treatment practices, 17/49 patients (35%) met operative criteria based on evidence-based guidelines but did not receive operative treatment by Malawian providers. For 7/17 (41%) of these patients, Malawian providers believed nonoperative treatment was ideal. In our educational course, 51/61 participants (84%) performed better between the pre- and post-course assessments. Overall scores improved from a mean of 66% to 77%, an improvement of 5.2/49 questions (95% CI 3.8-6.6, p<0.001). Providers could identify one more injury correctly out of 6 that were tested (95% CI 0.6-1.6, p<0.001), and identify one more ideal treatment out of 7 (95% CI 0.5-1.4, p<0.001). Conclusion: In Malawi, ankle fractures are common, and most are treated non-operatively. This is partly due to resource limitations, but also due to gaps in provider knowledge and lack of treatment standardization. Here we demonstrated a comprehensive approach to examining the challenges to providing adequate care, as well as the successful implementation of an intervention to improve care capacity nationwide.